Lung cancer incidence and mortality in trend and prediction between 2012-2030 in Shandong Province, using a Bayesian age-period-cohort model - Jiang, Fan; Fu, Zhentao; Chu, Jie; Ren, Jie; Xu, Chunxiao; Xu, Xiaohui; Guo, Xiaolei; Lu, Zilong; Xu, Aiqiang (Frontiers in Oncology, 2024)
ObjectivesLung cancer is one of the most common cancers in Shandong Province, China. Projecting future cancer trend is crucial for planning cancer control. We aimed to examine the trend of lung cancer incidence and mortality from 2012 to 2023, and predict the lung cancer burden to 2030 in Shandong.MethodsData of lung cancer incidence and mortality from 2012 to 2023 were obtained from the Shandong Cancer Registries. The average annual percentage change (AAPC) was used to quantify the trend of the lung cancer age-standardised rate using Joinpoint software. Bayesian age-period-cohort model was used to predict lung cancer incidence and mortality from 2024 to 2030.ResultsThe age-standardised incidence rate (ASIR) remained stable from 2012 to 2023. The ASIR in males decreased with an AAPC of -1.350%, while the ASIR in females increased with an AAPC of 2.429%. The age-standardised mortality rate (ASMR) decreased with an AAPC of -2.911%. This trend was also observed in males (AAPC=-2.513%), females (AAPC=-3.632%), urban areas (AAPC=-3.267%) and rural areas (AAPC=-2.603%). For our predictions, the ASIR will increase to 49.21 per 100,000 until 2030, with an AAPC of 1.873%. This upward trend is expected for females and urban areas, with an AAPC of 4.496% and 4.176%, while it is not observed for males and rural areas. The ASMR is expected to remain stable up to 2030, and this trend will maintain both in males and females. The ASMR will exhibit an upward trend (AAPC=1.100%) in urban areas and a downward trend (AAPC=-0.915%) in rural areas.ConclusionThe ASIR of lung cancer will increase until 2030, while the ASMR of lung cancer is expected to remain stable in Shandong. It is necessary to take further preventive measures such as strengthening tobacco control, enhancing health education and expanding screening efforts.